Defunciones por autolisis en el Centro de Investigación de Ciencias Forenses de la ciudad de Loja - Vega Cabezas, Esther Marina (2021)
Autolysis is a very important but largely preventable public health problem. Visualized as an escape from a problem or a crisis that produces intense suffering, it is therefore important to communicate to the public through current records in order to initiate prevention plans. In the present investigation, we determined the main mechanism of autolysis, identified the most susceptible sex and age group, as well as the main predisposing factors related to deaths by autolysis registered at the Center for Research the Forensic Sciences in the periods 2016 to 2019, the same that were known through the forensic medical report. A descriptive, retrospective study was carried out, in which the population included deceased citizens who had resided in the province of Loja and Zamora Chinchipe; a total of 134 cases were obtained; in which hanging was determined to be the most common mechanism used; the most affected sex was male; among the age groups with the highest prevalence were those between 14 and 20 years of age, and the predisposing factors that led to this decision were love breakup and depression. Keywords: suicide, death, youth, mental health, public health.